The Effect of Steam Inhalation with Eucalyptus Aromatherapy on Respiratory Rate in Bronchial Asthma Patients - Lesania, Impun; adinda (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Asthma attacks can be treated with steam inhalation. This method aims to clear the airways and ease breathing by inhaling steam from a basin of hot water mixed with a few drops of eucalyptus oil. The purpose of this study was to determine the effect of steam inhalation with eucalyptus aromatherapy on respiratory rate in bronchial asthma patients in the Pesisir Tengah Community Health Center (Puskesmas), Pesisir Tengah District, Pesisir Barat Regency, in 2024. This quantitative study used a quasi-experimental design with a one-group pre-test-post-test approach. The population and sample in this study were all elementary school children with bronchial asthma in the Pesisir Tengah Community Health Center, Pesisir Tengah District, Pesisir Barat Regency, from January to April 2024. The sampling technique used was accidental sampling. Based on the statistical test, a p-value of 0.000 was obtained, or a p-value <0.05, so it can be concluded that there is an effect of steam inhalation with eucalyptus aromatherapy on respiratory frequency in bronchial asthma patients in the Pesisir Tengah Community Health Center Work Area, Pesisir Tengah District, Pesisir Barat Regency in 2024. The results of this study are expected to be used as health information material so that it can increase respondents' knowledge about the effect of steam inhalation with eucalyptus aromatherapy on respiratory frequency in bronchial asthma patients.